Pedagogy Over Technology: Animal-Themed Digital Games to Support Early Mathematics Learning - Fathanah, Nurul; Syarfina, Syarfina; Nadhirah, Nadhirah; Kamis, Kamis; Mahriza, Rita; Maisari, Sri (Atfaluna: Journal of Islamic Early Childhood Education, 2025)
This study aims to develop and evaluate